A Qualitative Examination of Continuing Bonds through Spiritual Experiences in Individuals Bereaved by Suicide - Jahn, Danielle R. (Religions, 2018)
Introduction: Suicide is a public health problem worldwide, and spiritual experiences may be important positive experiences or coping mechanisms for difficulties associated with surviving a suicide loss. Studies have found that continuing bonds through spiritual experiences are common among individuals bereaved by suicide. However, the literature lacks depth in understanding these experiences, such as sense of presence. Aims: The aim of this study was to qualitatively examine descriptions of continuing bonds through spiritual experiences after death by suicide. Method: A total of 1301 individuals bereaved by suicide provided 2443 free responses about their spiritual experiences based on four different prompts, which were analyzed using an inductive approach. Results: Nine common themes were identified, selected for interest, and reported: (1) a helpful sense of comfort; (2) a helpful sense of connection with the deceased; (3) intense sadness evoked by the spiritual experiences; (4) confusion regarding the spiritual experiences; (5) negative reminders of the deceased or negative meanings of spiritual experiences; (6) evidence of an afterlife; (7) general importance of the spiritual experiences' meaning; (8) impact of and on religious beliefs; and (9) others' responses to disclosure of suicide or spiritual experiences. Conclusion: For the overwhelming majority of participants, spiritual experiences such as a sense of presence have deep meaning and are often regarded as a positive source of healing and transformation after a suicide death.